Polypropylene Reinforced With Recycle Polyethylene Terephthalate As An Alternative Material For New Plastic Product - A. N. M., Rose; M. M., Noor; M. M., Rahman; M. R. M., Rejab (2008)
Polyethylene Terephthalate (PET) is one of the most important fibers for industrial application. High performance, low cost, and recyclables are the most attractive candidates for high strength fibers. This paper presents the best ratio of Polypropylene (PP) reinforced with recycle PET fiber, as an alternative material for new plastic product. It gives the high strength of Polypropylene reinforced with recycle PET fiber. PP was mixed with recycle PP fiber utilising the plastic mixer and injection mold machine. The samples were cut according to ASTM standard and tested by using universal testing equipment. The analyses were carried out by using 0% ~ 10% volume compositions of recycle PP fiber. The acquired results indicate that the composition of PP gives higher ultimate tensile strength. It can be seen that the strength of PP increases in the presence of PET. It reduces the manufacturing cost and uses as an alternative material to PP for industrial application.